Gas-phase hydrogen transfer reduction of α,β-unsaturated ketones on Mg-based catalysts - Di Cosimo, Juana Isabel (2004)
The gas-phase regioselective reduction of mesityl oxide to the allyl alcohol using 2-propanol as a hydrogen donor was studied at 523 K on basic MgO, MgAl0.33Ox and Cu0.05MgAl0.65Ox oxides. Catalysts were characterized using a variety of physical and spectroscopic techniques. The effect of contact time on the product distribution was determined in order to identify primary and secondary reaction pathways. Main reaction products from mesityl oxide conversion were the two allyl alcohol isomers (UOL, 4-methyl-3-penten-2-ol and 4-methyl-4-penten-2-ol), isomesityl oxide, methyl isobutyl ketone (MIBK), methyl isobutyl carbinol and C9 aldol condensation products. Bifunctional Cu0.05MgAl0.65Ox did not produce alcohols. Metallic Cu atoms readily decomposed 2-propanol forming acetone and mobile surface H atoms that selectively reduced the CC bond of mesityl oxide giving mainly MIBK. UOL formed on MgO at unusually high yields for a gas-phase reaction (40% at 523 K, 2-propanol/mesityl oxide = 5 and HLSV = 14 cm3/(h g)). UOL formation on MgO proceeds via a hydrogen transfer Meerwein–Ponndorf–Verley (MPV) mechanism without participation of surface H atoms from 2-propanol dissociation. Weak acid–strong base Mg2+O2− surface pairs efficiently promote formation of the six-atom cyclic intermediate required in the MPV mechanism for selectively reducing the CO bond of an unsaturated ketone to the corresponding allyl alcohol. In contrast, UOL yield on MgAl0.33Ox was always lower than 5%. UOL formation is hindered on MgAl0.33Ox because surface Al3+ sites decrease by dilution the density of Mg2+O2− pairs and concomitantly favor the adsorption of mesityl oxide via the CC bond, thereby promoting the selective formation of MIBK.